MINERALOGY AND ORE FORMATION CONDITIONS OF THE NAILY GOLD DEPOSIT (SOUTH URALS) - A.D. Smirnitskaya; E.A. Rozhkova; E.V. Belogub; K.A. Novoselov; M.V. Zabotina; M.A. Rassomakhin (Минералогия)
The paper examines mineralogy of noble metals and ore formation conditions at the Naily gold deposit (South Urals), which is hosted in pyrite-bearing talc-carbonate, chlorite-quartz-carbonate and quartz-carbonate metasomatites after serpentinites and rocks of a gabbrodiorite-plagiogranite complex. Based on microscopic and electron microscopic studies of polished sections and heavy concentrates, it is established that native gold and Au tellurides are the major Au minerals of veins, metasomatites after intermediate and felsic intrusive rocks and foliated serpentinites. Native gold occurs as: 1) inclusions in pyrite and rarely in chalcopyrite, 2) free particles associated with non-metallic minerals, which probably fill interstitions, 3) interstitial forms in pyrite aggregates often together with chalcopyrite, galena and sphalerite, and veinlets in hessite, 4) fine inclusions in tetradymite and 5) inclusions in limonite. Tellurides of noble metals include calaverite, petzite, hessite and an unidentified Ag and Pb sulfotelluride. Silver is also incorporated in acanthite and Hg-Ag-Sb-As, Pb-Bi-Ag and Cu-Ag-Pb-Bi sulfosalts. The Ag content of free native gold is 10–16 wt. % increasing to 20–24 wt. % in native gold in pyrite and in assemblage with hessite. Altaite, coloradoite and Ni and Pd tellurides are found in assemblages similar to noble metal mineralization. The formation temperature of chlorite from ore-bearing metasomatites is 339–392 °C. Fluid inclusions in quartz, calcite and albite are homogenized at a temperature range of 162–377 °C. The eutectic temperature (–23.5 °C) is typical of NaClKCl-H2O system. The ice melting temperature varies from –0.5 to –3.7 °C corresponding to salinity of 0.9– 6.0 wt. % NaCl-equiv.